The Impact of Green Marketing Mix on Green Customer Loyalty for Packaged Beverage Products - Prabandaru, Rahardian Mohamad Akbar Ario Hanung; Soepatini, S (Universitas Muhammadiyah Surakarta, 2024)
The trend of adopting a green economy and sustainable industry is increasingly prominent in this era, driven by stricter regulatory demands and growing public awareness of environmental sustainability. Companies are now more focused on environmentally friendly innovations and resource efficiency to meet high regulatory standards and the expectations of consumers who are increasingly concerned about the environmental impact of their products and services. To address the demands of regulations and environmentally conscious consumers, companies must adapt to a green and sustainable economy by producing eco-friendly products. This adaptation needs to be implemented across various industrial sectors, one of which is the packaged food and beverage sector, a significant industry in Indonesia. This study aims to analyze the influence of the green marketing mix (4Ps) on green customer loyalty, mediated by consumer satisfaction with green products, focusing on PT Ultrajaya Tbk. The research primarily tests the proposed hypotheses. The sample for this research consisted of 155 respondents who were selected based on certain criteria. The testing is conducted by examining causal relationships between variables using a quantitative or numerical approach with primary data.The collected data was then processed using the PLS application.This method can be defined as a causal quantitative research methodology. Statistical testing includes two main tests, namely the outer and inner models. The outer model consists of classical assumption tests, Measurement Model, validity tests, and reliability tests. Meanwhile, inner model testing includes hypothesis testing, Model Feasibility Test, Effect Size F square, and R square tests. In conclusion, the implementation of the green marketing mix can create consumer satisfaction with green products, which ultimately leads to green customer loyalty. (1)The Influence of Green Product on Green Customer Satisfaction : Green products have a positive and significant impact on green customer satisfaction. (2) The Influence of Green Price on Green Customer Satisfaction: Green pricing has a positive and significant effect on customer satisfaction. (3)The Influence of Green Place on Green Customer Satisfaction: Green place positively and significantly influences green customer satisfaction. (4) The Influence of Green Promotion on Green Customer Satisfaction:Green promotion has a positive and significant impact on green customer satisfaction(5) The Influence of Green Product on Green Customer Loyalty: Green products have a positive and significant impact on green customer loyalty. (6) The Influence of Green Price on Green Customer Loyalty: Green pricing does not directly have a significant impact on customer loyalty. (7) The Influence of Green Place on Green Customer Loyalty: Green place not have a direct significant impact on customer loyalty. (8)The Influence of Green Promotion on Green Customer Loyalty :Green promotion has a positive and significant impact on green customer loyalty. (9) The Influence of Green Customer Satisfaction on Green Customer Loyalty: Green customer satisfaction has a positive and significant influence on green customer loyalty. It is hoped that this research can contribute by providing insights and knowledge regarding the influence of the green marketing mix 4Ps on green customer loyalty within the field of marketing, especially in the context of green marketing. This study is expected to be beneficial for marketing practitioners, particularly in providing information on the application of the green marketing mix 4Ps towards green customer loyalty.